Demography of a Reintroduced Population of Evermann's Rock Ptarmigan in the Aleutian Islands - Kaler, Robb S.; Ebbert, Steve E.; Braun, Clait E.; Sandercock, Brett K. (My University, 2011)
We report results of a 4-year translocation effort to reestablish a breeding population of Evermann’s Rock Ptarmigan (Lagopus muta evermanni) in the Near Islands group of the western Aleutian Archipelago. Habitat restoration was completed by eradication of introduced foxes from Agattu Island by 1979. We captured and moved 75 ptarmigan from Attu Island to Agattu Island during 2003–2006, nd monitored 29 radio-marked females in the last 2 years of the study. We compared the demography of newly translocated birds (n 5 13) with resident birds established from translocations in previous years (n 5 16). Mortality risk was increased by translocation and 15% of females died within 2 weeks of release at Agattu Island. All surviving females attempted to nest but initiated clutches 8 days later in the breeding season and laid 1.5 fewer eggs per clutch than resident females. Probability of nest survival (x¯ 6 SE) was good for both translocated (0.72 6 0.17) and resident females (0.50 6 0.16), and renests were rare. Probability of brood survival was higher among translocated (0.85 6 0.14) than resident females (0.25 6 0.12), partly as a result of inclement weather in 2006. Fecundity, estimated as female fledglings per breeding female, was relatively low for both translocated (0.9 6 0.3)and resident females (0.3 6 0.2). No mortalities occurred among radio-marked female ptarmigan during the 10-week breeding season, and the probability of annual survival for females in 2005–2006 was between 0.38 and 0.75. Translocations were successful because females survived, successfully nested, and recruited offspring during the establishment stage. Post-release monitoring provided useful demographic data in this study and should be a key component of translocation programs for wildlife restoration. Future population surveys and additional translocations may be required to ensure long-term viability of the reintroduced population of ptarmigan at Agattu Island.
Keywords: Translocation; Introduced Population; Lagopus-Mutus; Nest Survival; Ptarmigan; Aleutian Archipelago